2019
DOI: 10.1111/coa.13281
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of ß‐catenin, WISP1 and TCF21 predicts disease‐specific survival and primary response against radio(chemo)therapy in patients with locally advanced squamous cell carcinomas of the head and neck

Abstract: Objective The objective of this study was to determine the prognostic and predictive impact of β‐catenin, TCF21 and WISP1 expression in patients with squamous cell carcinomas of the head and neck who underwent primary radiotherapy or concomitant chemoradiotherapy. Study design Prospective cohort study. Setting University hospital. Participants Protein expression profiles of β‐catenin, TCF21, WISP1 and p16 were determined by immunohistochemical analyses in tissue samples of 59 untreated patients. Expression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Notably, it was found that PHF20 and WDR5 directly bind to the WISP1 transcription sequence at the same site, but not the other four genes. By carrying out an in-depth investigation of the functions of WISP1 and BGN, we found a large number of reports linking these genes with the Wnt/β-Catenin signaling pathway (25,(37)(38)(39)(40)(41)(42). Consistently, our PPI analysis of WISP1 indicated that both WISP1 and BGN are closely associated with the Wnt/β-Catenin signaling pathway.…”
Section: Discussionsupporting
confidence: 70%
“…Notably, it was found that PHF20 and WDR5 directly bind to the WISP1 transcription sequence at the same site, but not the other four genes. By carrying out an in-depth investigation of the functions of WISP1 and BGN, we found a large number of reports linking these genes with the Wnt/β-Catenin signaling pathway (25,(37)(38)(39)(40)(41)(42). Consistently, our PPI analysis of WISP1 indicated that both WISP1 and BGN are closely associated with the Wnt/β-Catenin signaling pathway.…”
Section: Discussionsupporting
confidence: 70%
“…This picture in melanoma further strengthens the tumor-facilitating role of CCN4. In a study on head and neck cancer squamous cell carcinoma Vyskocil et al (2019) sought to determine the prognostic and predictive impact of β-catenin, TCF21 and CCN4 expression in 59 untreated patients, with squamous cell carcinomas, who then underwent primary radiotherapy or concomitant chemoradiotherapy. In this prospective cohort study the impact of TNM classification, grading, sex, age, gender, type of therapy, response to therapy and p16 status on disease-specific (DSS) and disease-free survival (DFS) was analyzed.…”
Section: Ccn4mentioning
confidence: 99%
“…189 HNSCC patients underwent RT between May 2005 and August 2008 at the Vienna General Hospital, Austria [ 12 , 13 , 14 ] and were therefore evaluated for eligibility. Those with missing data, the occurrence of recurrence, or insufficient follow-up time of fewer than 60 months were initially excluded ( n = 91).…”
Section: Methodsmentioning
confidence: 99%